Stabilization, Safety, and Security of Distributed Systems 18th International Symposium, SSS 2016, Lyon, France, November 7-10, 2016, Proceedings - Bonakdarpour, Borzoo; Petit, Franck (Theoretical Computer Science and General Issues, 2016)
This book constitutes the refereed proceedings of the 18th International Symposium on Stabilization, Safety, and Security of Distributed Systems, SSS 2016, held in Lyon, France, in November 2016. This year the Program Committee was organized into three groups reflecting the major trends related to self-* systems: (a) Self-* and Autonomic Computing, (b)Foundations, and (c) Networks, Multi-Agent Systems, and Mobility.